2021
DOI: 10.4236/ars.2021.103004
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Reflectance Characteristics of Cyanobacteria

Abstract: Potentially harmful cyanobacterial blooms are an emerging environmental concern in freshwater bodies worldwide. Cyanobacterial blooms are generally caused by high nutrient inputs and warm, still waters and have been appearing with increasing frequency in water bodies used for drinking water supply and recreation, a problem which will likely worsen with a warming climate. Cyanobacterial blooms are composed of genera with known biological pigments and can be distinguished and analyzed via hyperspectral image col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In-situ hyperspectral reflectance data were qualitatively compared with in-situ chlorophyll-a, phycocyanin, turbidity, and Secchi depth data to evaluate the hyperspectral reflectance observed for the Grapevine Lake sampling sites. Hyperspectral reflectance data were used to explore the optical signatures of algae and cyanobacteria pigments, chlorophyll-a, and phycocyanin, entrained in or accumulating on the water surface to aid in the interpretation of what portion of the spectrum might be most valuable for highly performing spectral indices 57 . Hyperspectral reflectance data of the water surface were obtained using an ASD HandHeld 2 visible NIR, 400 to 900 nm, spectroradiometer 58 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In-situ hyperspectral reflectance data were qualitatively compared with in-situ chlorophyll-a, phycocyanin, turbidity, and Secchi depth data to evaluate the hyperspectral reflectance observed for the Grapevine Lake sampling sites. Hyperspectral reflectance data were used to explore the optical signatures of algae and cyanobacteria pigments, chlorophyll-a, and phycocyanin, entrained in or accumulating on the water surface to aid in the interpretation of what portion of the spectrum might be most valuable for highly performing spectral indices 57 . Hyperspectral reflectance data of the water surface were obtained using an ASD HandHeld 2 visible NIR, 400 to 900 nm, spectroradiometer 58 .…”
Section: Methodsmentioning
confidence: 99%
“…Hyperspectral reflectance data were used to explore the optical signatures of algae and cyanobacteria pigments, chlorophyll-a, and phycocyanin, entrained in or accumulating on the water surface to aid in the interpretation of what portion of the spectrum might be most valuable for highly performing spectral indices. 57 Hyperspectral reflectance data of the water surface were obtained using an ASD HandHeld 2 visible NIR, 400 to 900 nm, spectroradiometer. 58 Boat shadows and sun glint were avoided during the collection of spectral reflectance signatures.…”
Section: Field Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all algae are harmful, but a capacity to identify those that are potentially toxic could more effectively inform management actions. A plausible way forward was pioneered by Paine et al [56] and Slonecker et al [57], who showed that reflectance spectra measured in a lab while viewing algal samples under a microscope could be used to distinguish between taxa. Slonecker et al [58] have already published a spectral library consisting of 13 genera that is freely available to support this type of work; these authors plan to expand the library to include additional taxa [57].…”
Section: Advancing the Remote Sensing Of Benthic Algaementioning
confidence: 99%
“…A plausible way forward was pioneered by Paine et al [56] and Slonecker et al [57], who showed that reflectance spectra measured in a lab while viewing algal samples under a microscope could be used to distinguish between taxa. Slonecker et al [58] have already published a spectral library consisting of 13 genera that is freely available to support this type of work; these authors plan to expand the library to include additional taxa [57]. A logical next step toward a hyperspectral approach to algal mapping might involve acquiring hyperspectral images from a UAS in coordination with the collection of field samples processed for biomass and taxonomy.…”
Section: Advancing the Remote Sensing Of Benthic Algaementioning
confidence: 99%